Development of a core outcome set for lower limb orthopaedic surgical interventions in ambulant children and young people with cerebral palsy - Almoajil, H (2022)
Background: The literature on lower limb orthopaedic surgery for ambulant children with cerebral palsy (CP) demonstrates significantly heterogenous outcomes and outcome measures and evidence of selective outcome reporting. This limits evidence synthesis and undermines research findings through outcome reporting bias. Although several outcomes are commonly measured and reported, these do not always capture the needs and expectations of children and families.